Transformasi Spiritual Santri Melalui Program Quantum Tahfidz Ash-Shiddiiqi - Iskandar Purnama (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to describe the implementation of the Quantum Tahfidz Ash-Shiddiiqi (QTA) program at Ash-Shiddiiqi Islamic Boarding School, analyze the forms of students' spiritual transformation through the program, and identify the supporting and inhibiting factors of the transformation. This research employs a qualitative approach with a descriptive research type. Primary data were collected through interviews and observations of students, muhafidz (mentors), and program administrators. Secondary data were obtained from books, journals, pesantren documents, and activity archives. The findings reveal that the QTA program is implemented through structured stages including tahsin (recitation improvement), tahfidz (memorization), halaqah (learning circles), habituation of worship, and character reinforcement. Students' spiritual transformation encompasses four dimensions: faith, worship, morals, and self-awareness. Supporting factors include student motivation, religious environment, and muhafidz role modeling, while inhibiting factors include lack of motivation, boredom, time constraints, and uneven quality of muhafidz. The QTA program is proven to play a significant role in fostering students' holistic spiritual transformation.